Bioaccumulation of Cadmium (Cd) Heavy Metal on Seaweed (Gracilaria sp.) in Traditional Fishpond of Jabon Subdistrict, Sidoarjo District. (February 2019) - Ardiyansyah, O; Sudarno,; Rosmanida,
Abstract: Contamination of poisonous chemical substance is the main problem of every country, one of them is cadmium (Cd). Cd is heavy metal with high mobility from the environment to organisms, especially plants, and will have effect on the food chain. Gracilaria sp. is one of the biota capable of accumulating heavy metals through adsorption on the surface of talus in the form of cations, anions, or organic compounds. The high Cd content in the environment will lead to the higher amount of Cd accumulated by Gracilaria sp. This research aims to learn the bioaccumulation of Cd in seaweed (Gracilaria sp.), water, and sediment in Traditional Fishpon of Jabon Subdistrict, Sidoarjo District. This study used observation method, examination of Cd content using Atomic Absorption Spectrophotometry (AAS), and data analysis using the same method. The result of analysis of Cd content in fishpond water with an average of 0.0144 mg/l surpasses the 0.01 mg/l threshold established by Research Regulation Number 82 (2001), Cd content in sediment and Gracilaria sp. is <0.0024 mg/kg and is below the 0.2 mg/kg threshold established by BSN (2009).